2020
DOI: 10.15561/20755279.2020.0301
|View full text |Cite
|
Sign up to set email alerts
|

Four-week of local electromyostimulaiton training on fingerboard increases the isokinetic wrist strength and endurance

Abstract: Background and Study Aim: Electromyostimulaiton (EMS) has been used for both physical therapy and strength improvements for a few decades. This study aimed to investigate the effects of a four-week local-EMS training performed on a fingerboard (FT) in wrist strength and endurance. Material and Methods:  Sixteen physically active, non-climber students were divided into EMS+FT and FT groups. Each group performed the same training program about 25 min a day, 3 days a week for four weeks. The EMS+FT implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…It is especially critical for sports involving throwing, jumping, and short distance sprints that require explosive properties. Many studies have been conducted to develop and evaluate strength and power (Aras et al, 2020;Güçlüöver & Gülü, 2020). It is of great importance to determine the dominant/nondominant, agonist/antagonist strength differences and to plan exercises in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially critical for sports involving throwing, jumping, and short distance sprints that require explosive properties. Many studies have been conducted to develop and evaluate strength and power (Aras et al, 2020;Güçlüöver & Gülü, 2020). It is of great importance to determine the dominant/nondominant, agonist/antagonist strength differences and to plan exercises in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising findings, the application of NMES in climbing remains relatively unexplored. To the best of the authors' knowledge, only one study has focused on NMES training in climbing [34]. This study demonstrated significantly improved isokinetic wrist strength and endurance using NMES-supported fingerboard training compared with the strength and endurance observed with conventional fingerboard training.…”
Section: Introductionmentioning
confidence: 67%
“…This implies the need to develop injury prevention programs. Currently, techniques for the prevention of injuries in rock climbing are beginning to be developed [7,8]. Therefore, literature data on the prevention of injuries in rock climbing are insufficient.…”
Section: Introductionmentioning
confidence: 99%